Esterification of phenyl acetic acid with p-cresol using metal cation exchanged montmorillonite nanoclay catalysts. Issue 2 (7th February 2018) - Bhaskar, M.; Surekha, M.; Suma, N.
Abstract : The liquid phase esterification of phenyl acetic acid with p -cresol over different metal cation exchanged montmorillonite nanoclays yields p -cresyl phenyl acetate. Different metal cation exchanged montmorillonite nanoclays (M n + = Al 3+, Zn 2+, Mn 2+, Fe 3+, Cu 2+ ) were prepared and the catalytic activity was studied. The esterification reaction was conducted by varying molar ratio of the reactants, reaction time and catalyst amount on the yield of the ester. Among the different metal cation exchanged catalysts used, Al 3+ -montmorillonite nanoclay was found to be more active. The characterization of the material used was studied under different techniques, namely X-ray diffraction, scanning electron microscopy and thermogravimetric analysis. The product obtained, p -cresyl phenyl acetate, was identified by thin-layer chromotography and confirmed by Fourier transform infrared, 1 H NMR and 13 C NMR. The regeneration activity of used catalyst was also investigated up to fourth generation.